(untitled) (Damascus University Journal for engineering sciences, 2024)
Summary Despite the development witnessed by the world in all aspects of life, whose revolution we see in the field of architecture and interior design in particular, it did not do justice to the category of people with special needs in general and those with special needs (the blind) in particular, which led to their restriction and the obligation of their families to accompany them to practice their lives naturally and smoothly and activate their role in building the society. Where the research will provide a clear definition of this category of people with special needs (the blind) and identify their different categories and also learn about Braille as it is the only language in the world that helps the (blind) and identify some of the vocabulary and elements in the interior design that will help the (blind) in understanding the interior spaces It contributes to his integration into his society, analyzing some of the designs that created solutions and using them to find basic standards in interior design to take into account this category of people with special needs.